Changes in myofibrillar components after skeletal muscle necrosis induced by a myotoxin isolated from the venom of the snake bothrops asper - Gutiérrez, José María (1990)
The effects of a myotoxic phospholipase A2 isolated from the venom of the crotaline snake Bothrops asper on skeletal muscle myofibrils were studied by histological, ultrastructural, immunohistochemical, and biochemical parameters. Myotoxin induced a rapid and prominent muscle necrosis after intramuscular injection in mice. In this process, myofibrils were affected and three main changes were observed: (A) Initially, they were hypercontracted, eventually forming “clumped,” dense masses which alternated with spaces devoid of myofilaments in the cytoplasm. This initial stage is probably due to hypercontraction resulting from a calcium influx after toxin-induced sarcolemmal damage. (B) A second change occurred between 3 and 6 hr, when the clumped or hypercontracted pattern changed to a “hyaline” pattern in which myofilaments were relaxed and had a more uniform distribution in the cellular space. Although there was not a widespread degradation of myofibrillar components at this stage, desmin started to be lost in samples obtained as early as 15 min after toxin injection, and α-actinin was almost absent by 7 hr. Thus, it is proposed that this shift may be due to a selective proteolytic degradation of structurally relevant components, particularly α-actinin. As a consequence, the mechanical integration of myofilaments is impaired, precluding hypercontraction. (C) Finally, at later time periods (24, 48, and 72 hr), there was widespread degradation of myofibrillar proteins, probably caused by proteases derived from inflammatory cells such as neutrophils and macrophages, whose numbers in necrotic muscle increased markedly at these time periods.